A Case of Colon Metastasis from Gastric Cancer Treated by Laparoscopic-Assisted Segmental Colectomy - Kawada, Junji; Nomura, Tomonori; Mizuno, Manatsu; Fukada, Akio; Nakano, Masaya; Kidogami, Shinya; Taniguchi, Yoshiki; Asukai, Kei; Osawa, Hideki; Mokutani, Yukako; Kishimoto, Tomoya; Hirose, Hajime; et al. (Gan to kagaku ryoho, 2023)
We report a case of colon metastasis from gastric cancer treated by laparoscopic-assisted segmental colectomy. An 81-year-old man was undergone distal gastrectomy, D2 dissection and Billroth Ⅰ reconstruction for gastric cancer 3 years previously, with a final diagnosis of gastric cancer L, Post, Type 2, sig/por2, pT4a(SE), pN3b(30/56), H0, P0, M0, pStage ⅢC. Three years after gastrectomy, CT scan showed an elevated lesion in the transverse colon, which was suspected to be metastatic colorectal cancer on closer examination. As no metastatic lesions were found other than the tumor of transverse colon, we performed laparoscopic-assisted segmental colon resection. A small incision was placed in the umbilical region, and the transverse colon was extracted from the umbilical region after dissection of the adhesions by single-incision laparoscopic surgery. The transverse colon containing the mass lesion was partially resected extracorporeally and reconstructed with a functional end-to-end anastomosis. The postoperative pathological findings revealed tumor cells predominantly below the submucosal layer and partly showing the signet ring cell carcinoma, and the transvers colon tumor was diagnosed as a metastasis from gastric cancer. The postoperative course was uneventful and the patient was discharged 8 days after surgery, and is alive for 10 months after the segmental colon resection followed by chemotherapy.